2019
DOI: 10.1055/s-0039-1692723
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Executive Function Performance in Preschoolers with Developmental Language Disorder

Abstract: Although results vary across individual studies, a large body of evidence suggests that children with developmental language disorder (DLD) have domain-general deficits in executive function compared with peers with typically developing language. Poorer performance for children with DLD has been reported on verbal and nonverbal measures of sustained selective attention, working memory, inhibition, and shifting. However, examination of the variability of task scores among both children with and without DLD reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 51 publications
0
10
0
1
Order By: Relevance
“…For accomplishing language production: the individual must use long-term memory, to remember and apply the rules; working memory, to keep track of what one said and what is being said by others; attention, for focusing on the message that is being received; and inhibition, to adhere to the rules or to switch from one language to another in the case of multilingualism [ 5 , 6 , 31 ]. These might be the reason why EF deficits are very common in children with SLI when compared with their TD peers; in our review, we found that studies report some type of alteration in EF (assessed by different tests, Table 2 ) in 62%-91% of cases [ 13 , 14 , 17 - 21 , 23 - 25 , 27 , 28 , 30 ].…”
Section: Reviewmentioning
confidence: 81%
See 2 more Smart Citations
“…For accomplishing language production: the individual must use long-term memory, to remember and apply the rules; working memory, to keep track of what one said and what is being said by others; attention, for focusing on the message that is being received; and inhibition, to adhere to the rules or to switch from one language to another in the case of multilingualism [ 5 , 6 , 31 ]. These might be the reason why EF deficits are very common in children with SLI when compared with their TD peers; in our review, we found that studies report some type of alteration in EF (assessed by different tests, Table 2 ) in 62%-91% of cases [ 13 , 14 , 17 - 21 , 23 - 25 , 27 , 28 , 30 ].…”
Section: Reviewmentioning
confidence: 81%
“…Reichenbach (2016) [20] Cross-Sectional Low Kapa (2019) [21] Cross-Sectional Moderate Marton (2014) [22] Cross-Sectional Moderate Quintero (2013) [23] Cross-Sectional Low Im-Bolter (2006) [24] Cross-Sectional Low Schuchardt (2013) [25] Cross-Sectional Low Acosta (2015) [26] Cross-Sectional Low Roello (2014) [27] Cross-Sectional Moderate Vugs (2015) [28] Cross-Sectional Low…”
Section: Figure 1: Prisma Flowchartmentioning
confidence: 99%
See 1 more Smart Citation
“…GDB olan bireylerin yaşadıkları dil sorunları zihinsel yetersizlik, işitme kaybı, motor bozukluklar, herhangi bir nörolojik bozukluk (Botting & Conti-Ramsden, 2003) ya da otizm spektrum bozukluğu, beyin hasarı sonucu ortaya çıkan güçlükler, epileptik afazi gibi biyomedikal faktörlere bağlı olmaksızın ortaya çıkmaktadır (Özcebe vd., 2019). Bununla birlikte GDB olan çocukların muhakeme etmede, akıl yürütmede ve yürütücü işlevler gerektiren görevleri yerine getirmede zorlandıkları bilinmektedir (Kapa & Erikson, 2019;Krzemien vd., 2019). GDB'yi açıklayabilmek adına genetik, nörobiyolojik ve bilişsel faktörler araştırılmaya devam edilmektedir.…”
Section: Introductionunclassified
“…Language problems experienced by children with DLD arise when mental disability, hearing loss, motor disorders, any neurological disorder (Botting & Conti-Ramsden, 2003) or autism spectrum disorder, difficulties resulting from brain damage, biomedical factors, such as epileptic aphasia are excluded (Özcebe et al, 2019). However, children with DLD have difficulties in reasoning and performing tasks that require executive functions (Kapa & Erikson, 2019;Krzemien et al, 2019). In order to explain DLD, genetic (Leonard, 2000), neurobiological (Korkmaz, 2005) and cognitive factors continue to be investigated.…”
Section: Introductionmentioning
confidence: 99%